EFISIENSI MODAL INTELEKTUAL DAN DAMPAKNYA TERHADAP KINERJA PERUSAHAAN - Istianingsih Istianingsih (Akuntabilitas, 2014)
This study aimed to analyze the effect of intellectual capital efficiency of thefinancial performance and the performance of the company's shares. Measurement offinancial performance with return on equity (ROE), earnings per share (EPS), while thecompany's stock performance is measured by the cumulative abnormal return (CAR). Thetotal sample in this study was 108 companies and individual company data taken 3 years from2009 to 2011. The hypothesis testing with multiple linear regression method. Results from thisstudy showed that the intellectual capital positive effect on ROE and EPS. However,intellectual capital is not proven effect on CAR. The main implication of this study for themanagement of the company for more attention to the management of intellectual capitalbecause it is proven to improve the performance of the companyDOI: 10.15408/akt.v7i3.2731